1998
DOI: 10.1159/000015148
|View full text |Cite
|
Sign up to set email alerts
|

High resolution RBA-banding comparison between early prometaphase chromosomes of cattle (<i>Bos taurus</i> L.) and goat (<i>Capra hircus</i> L.) at 700 band level

Abstract: High resolution RBA-banded early prometaphase chromosomes of cattle (Bos taurus L.) and goat (Capra hircus L.), from thymidine synchronized lymphocyte cultures, are compared at a level of 700 bands per haploid genome, with the purpose of detecting the extent of banding homologies between the two species and improving the resolution level of the ISCNDA (1989) standardized RBA-banded karyotypes. The results demonstrate that, at this level of resolution, at least 10 autosomes can be fully homologized between the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…Because of the close similarity among bovine, caprine and ovine karyotypes (Evans et al, 1973;Schnedl and Czaker, 1974;Hayes et al, 1991;Kaftanovskaya and Serov, 1994;Iannuzzi and Di Meo, 1995;Di Berardino and Burguete, 1998), the data accumulated for cattle can serve as a basis to define the International System for Chromosome Nomenclature of Domestic Bovids. This will contribute essential material for all cytogeneticists interested in gene mapping and comparative mapping, analysing chromosome rearrangements or studying the chromosome phylogeny of bovidae species.…”
Section: Resultsmentioning
confidence: 99%
“…Because of the close similarity among bovine, caprine and ovine karyotypes (Evans et al, 1973;Schnedl and Czaker, 1974;Hayes et al, 1991;Kaftanovskaya and Serov, 1994;Iannuzzi and Di Meo, 1995;Di Berardino and Burguete, 1998), the data accumulated for cattle can serve as a basis to define the International System for Chromosome Nomenclature of Domestic Bovids. This will contribute essential material for all cytogeneticists interested in gene mapping and comparative mapping, analysing chromosome rearrangements or studying the chromosome phylogeny of bovidae species.…”
Section: Resultsmentioning
confidence: 99%
“…For this reason, sheep ideograms have been modified as compared to those reported by Ansari et al (1999) so that band numbering, band intensities and landmarks are as close as possible to those of bovine ideograms. Since cattle and goat banded chromosomes (Hayes et al, 1991;Iannuzzi and Di Meo, 1995;Di Berardino and Burghete, 1998) are very similar, most cattle G-and R-banded ideograms can be applied to goat chromosomes. However, due to small differences in the band pattern of a few chromosomes, sheep ideograms of chromosomes 8, 9, X and Y should be used for goat chromosomes 9, 14, X and Y.…”
Section: Standard Karyotypes and Ideogramsmentioning
confidence: 99%
“…Comparative chromosome banding studies have demonstrated extensive chromosome (arm) homoeology among bovids, especially in the autosomes (Buckland and Evans, 1978;Hayes et al, 1991;Gallagher and Womack, 1992;Kaftanovskaya and Serov, 1994;Iannuzzi and Di Meo, 1995;Di Berardino and Burghete, 1998). These homoeologies have been confirmed by both comparative FISH mapping (Hayes et al, 1993;Iannuzzi et al, 1993Iannuzzi et al, , 1999aIannuzzi et al, , 2000aLopez-Corrales et al, 1998) and linkage mapping studies (Crawford et al, 1995;de Gortari et al, 1998).…”
Section: Copyright © 2001 S Karger Ag Baselmentioning
confidence: 90%